Environmental radioactive contamination and its effects on the spread of cancer in the province of Baghdad (Amal Hospital model) - عاكَول منخي سعدية; سعيد داود انفال (Al-Adab Journal, 2018)
Pollution means an imbalance in the movement that arise between the group consisting of ecosystem elements, and in line this imbalance to enter the production and consumption waste toward ecosystem sizes and types outweigh its ability to self-purification of especially toxic substances or complex that are difficult to deal with them, leading to prejudice in harmonic motion between the elements. And radioactive contamination of the most dangerous types of pollution which defined rights and is dangerous in infiltrating into the human body and different organisms without warning, as he does not see and does not feel and does not smell, as it is easily spread in the air, soil and water, and the injury is directly connecting Such as inhalation air to the lungs and then to the cells and tissues of the body, as well as through the skin due to a wound or incision in the human body. And the most severe radioactive contamination damage What affects the genetic material (DNA) in the organism causing mutations lead in the end to cause trouble in the genetic and the qualities that appear in the image defects and certain diseases passed down the generations, as happened in Hiroshima and Nagasaki in Japan and Chernobyl in the Soviet Union . The radioactive contamination in Iraq, particularly in the study of Baghdad region has resulted from the recent wars since 1991 until 2003 as a result of the use of US forces and its allies uranium munitions which cause environmental disasters and health and tent were the results the spread of cancer, and the Ministry of Environment has indicated the presence of more than 300 site in Iraq and (5 sites) more polluted with pesticides Alzenbakah and heavy elements multi-phenol and chlorine and depleted uranium because of abandoned weapons in some areas after the end of wars and chromium sulfate and cyanide and sulfur and its compounds fourth Othilat lead, and depleted uranium affects Public Health and guide noticeable shifts in injury rates of birth defects and cancers striking in Baghdad disease (the study area) during the last period and especially the period (1991-2011).